Designing and Evaluating XR Cultural Heritage Applications Through Human–Computer Interaction Methods: Insights from Ten International Case Studies. - Tromp, Jolanda; Schofield, Damian; Parvari, Pezhman Raeisian; Poyade, Matthieu; Eaglesham, Claire; Torres, Juan Carlos; Johnson, Theodore; Jürivete, Teele; Lauer, Nathan; Reyes-Lecuona, Arcadio; González-Toledo, Daniel; Cuevas-Rodríguez, María; et al. (MDPI, 2025)
Advanced three-dimensional extended reality (XR) technologies are highly suitable for cultural heritage research and education. XR tools enable the creation of realistic virtual or augmented reality applications for curating and disseminating information about cultural artifacts and sites. Developing XR applications for cultural heritage requires interdisciplinary collaboration involving strong teamwork and soft skills to manage user requirements, system specifications, and design cycles. Given the diverse end-users, achieving high precision, accuracy, and efficiency in information management and user experience is crucial. Human–computer interaction (HCI) design and evaluation methods are essential for ensuring usability and return on investment. This article presents ten case studies of cultural heritage software projects, illustrating the interdisciplinary work between computer science and HCI design. Students from institutions such as the State University of New York (USA), Glasgow School of Art (UK), University of Granada (Spain), University of Málaga (Spain), Duy Tan University (Vietnam), Imperial College London (UK), Research University Institute of Communication & Computer Systems (Greece), Technical University of Košice (Slovakia), and Indiana University (USA) contributed to creating, assessing, and improving the usability of these diverse cultural heritage applications. The results include a structured typology of CH XR application scenarios, detailed insights into design and evaluation practices across ten international use cases, and a development framework that supports interdisciplinary collaboration and stakeholder integration in phygital cultural heritage projects.
Keywords: Interacción hombre-ordenador; Museos - Innovaciones tecnológicas; Museos y educación; Patrimonio cultural; Extended reality; Cultural heritage; Usability; Pedagogy; Museum exhibits; DoE